Reclaiming Betawi Identity: A Critical Discourse Analysis of Si Doel Anak Sekolahan Original Soundtrack - Pratiwi, Cysakaren Diva; Riyanto, Edi Dwi; Meyrasyawati, Dewi (Fakultas Bahasa dan Seni, 2025)
This article analyzes the cultural significance of the theme song of Si Doel Anak Sekolahan using an ethnomusicological approach, specifically focusing on the representation of Betawi society. The main problem addressed is how the song's lyrics reflect the identity, values, and social changes of the Betawi people within an urban context. Additionally, this study explores how music functions as a form of cultural storytelling, representing the daily experiences and social dynamics of the Betawi community. This research aims to understand the role of music as a medium of cultural expression that mirrors social realities while preserving cultural identity in the face of modernization. The method used is a qualitative lyrical text analysis to identify prominent cultural themes. The findings reveal that the lyrics are not merely entertainment but also a means to reinforce community identity and reflect complex social dynamics.